Analysis of Risk Factors affecting Stunting at Sub-District Health Center Galesong Takalar Regency - Andi Maryam; Andi Elis; Yusriadi Yusriadi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Stunting (short) is a linear growth disorder caused by malnutrition of chronic nutrient intake or chronicor recurrent infectious diseases indicated by a z-score of height by age (TB/U) of less than -2 elementaryschool. The purpose of this study is to find out the analysis of risk factors that affect stunting in Sub-DistrictHealth Center Galesong Takalar Regency. The types of research used in this study are stunting case studiesin toddlers as dependent variables whereas the independent variables studied are birth weight, energy intake,protein intake, age and gender of toddlers, maternal education, number of household members, residentialareas and family economic status. The sample is a baby that has complete data according to the researchvariables (nothing is missing). As recorded in Sub-District Health Center Galesong Takalar Regency 2019using Lemesshow formula N = 298. The results showed that psychosocial stimulation affects stuntingproblems with a risk of 33.84 times. These results showed that the four free variables tested found nocorrelation with each other, so they were declared free of multicollinearity.